2001
DOI: 10.1111/j.1751-0813.2001.tb10751.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of equine herpesviruses 1 and 4 by polymerase chain reaction

Abstract: Individual single round and second round (seminested) PCRs and a seminested multiplex PCR were developed that enabled reliable, rapid detection of EHV1 and EHV4 in aborted foetal tissues and nasopharyngeal swab samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 23 publications
(23 reference statements)
0
37
0
7
Order By: Relevance
“…The sensitivity of the PCR used was higher when compared with similar data presented by Varrasso et al (2001) who found that their glycoprotein H gene-based PCR was able to detect 1220 and 7280 plasmid EHV1 and EHV4 DNA copies, respectively. The authors increased the sensitivity of the assay by adding a second amplification cycle using nested primers.…”
Section: Discussionmentioning
confidence: 69%
“…The sensitivity of the PCR used was higher when compared with similar data presented by Varrasso et al (2001) who found that their glycoprotein H gene-based PCR was able to detect 1220 and 7280 plasmid EHV1 and EHV4 DNA copies, respectively. The authors increased the sensitivity of the assay by adding a second amplification cycle using nested primers.…”
Section: Discussionmentioning
confidence: 69%
“…As amostras negativas para o vírus da raiva foram enviadas ao Laboratório de Patologia Molecular da Escola de Veterinária da UFMG para o diagnóstico através de PCR específicos para EHV-1 e EHV-4 (Varrasso et al, 2001), SHV-1 (Fonseca Jr. et al, 2011) ou RT-PCR para as seguintes arboviroses: SLEV (Ré et al, 2008), WNV, EEEV (Johnson et al, 2003), WEEV e VEEV (Eshoo et al, 2007). Para a extração do DNA/RNA total, as amostras de fragmentos de SNC (córtex, cerebelo, hipocampo, tálamo e medula) foram suspensas em solução salina tamponada a 20% (p/v) e livre de DNA e RNA, homogeneizadas e centrifugadas a 2.000 x g, a 4 o C, por 30 minutos.…”
Section: Methodsunclassified
“…A segunda reação dos semi-nested PCR (EHV-1 e 4) foi feita utilizando-se a mesma concentração dos reagentes da primeira reação e adicionando-se como amplicon, 1μL da primeira reação. Os oligonucleotídeos iniciadores específicos utilizados para detecção dos EHV-1, EHV-4 e SHV-1 foram desenhados e descritos previamente (Varrasso et al, 2001;Fonseca Jr. et al, 2011). Para assegurar a qualidade das amostras de DNA, foi realizada amplificação de parte do gene do fator de crescimento semelhante à insulina 1 (IGF-1), altamente conservado em mamíferos (Mikawa et al, 1995), sob condições previamente descritas (Costa et al, 2009).…”
Section: Methodsunclassified
See 2 more Smart Citations